Gut in the Womb - Gadre, Sandhya Subhash (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Dilatation and curettage is one of the common minor procedures with minimal complications but it can cause major complications like perforation of uterus, which is a surgical emergency and the delay in diagnosis and treatment has deleterious consequences for the mother. We are reporting this case of intestinal evisceration & its strangulation in puerpera after surgical evacuation for retained product of conception. This case is reported as evacuation is a commonly done procedure in puerperium for management of secondary PPH, hence want to emphasize that delay in the diagnosis of complications and management can lead to grave prognosis of the mother.